Education and Equality in Japan. - Cummings, William K. (Princeton : Princeton University Press, 2014)
On the basis of direct personal observation in the classroom, systematically gathered data, and extensive reading in primary sources, the author provides a rich description of how a society can be gradually transformed by the educational process in its schools. He then relates this process to the problems of the advanced industrial world. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback ed.
Frontmatter -- Contents -- List of Tables -- List of Figures -- Preface and Acknowledgments -- One. Transforming Society by Education -- Two. The Background for Change -- Three. The Government and the Teachers' Union -- Four. The Importance of Class and Family -- Five. Egalitarian Education -- Six. Cognitive Equality -- Appendix to Chapter Six -- Seven. The Development of the Egalitarian Sentiment -- Eight. The Examination Competition -- Nine. Equalizing Society -- Ten. The Lessons of Japanese Education -- Bibliography -- Index
Print version record.
Cover.
JSTOR
Keywords: Education -- Japan -- History -- 1945-; Educational equalization -- Japan -- History -- 20th century; Éducation -- Japon -- Histoire -- 1945-; Démocratisation de l'enseignement -- Japon -- Histoire -- 20e siècle.; EDUCATION -- Essays; EDUCATION -- Organizations & Institutions; EDUCATION -- Reference; HISTORY -- Asia -- Japan; Education; Educational equalization; Japan; Since 1900; Electronic books; History